A Commentary on Corporate Social Responsibility and Natural Disasters in India. (September 2017) - Kumar, Arvind
The purpose of this study was to evaluate the role of top 100 Indian companies in natural disasters and identify best practices of corporations in India. Results are derived from secondary data collected from websites, newsletters and annual reports of the companies. Three natural disasters were taken for the study from the year 2013–15. It is observed that most of the companies have been engaged in disaster relief activities for social and ethical reasoning. These activities included financial help, stake holder consultation and partnerships with NGOs, non-profit organizations (NPOs) and the government. Corporations also help in disaster management simply by engaging in their regular business. This study analyzes the role of corporations in natural disasters from a corporate social responsibility (CSR) perspective and discusses the possible way of coping with natural disasters by Indian companies. The research findings will be very useful for Indian companies, Confederation of Indian Industries (CII), National Disaster Management Authority (NDMA), and Government, after the enactment of Companies Act 2013. It would be very helpful for normalcy of human life and business. It analyses only top 100 Indian company's contribution. It lacks the reflections of the other countries.